Colloquium on Hermeneutics - Funk, Robert W. (Theology today, 1964)
“It is as if, all of a sudden, the things our theological tradition took for granted can no longer be taken for granted. Reality as the post-war generation experiences it does not permit the easy affirmation of some traditional starting point, in relation to which the theological enterprise can be newly ordered; rather, it senses the necessity to take nothing as the presupposition (least of all God or faith) of its theological endeavor. In this connection it should be observed that there is a new and radically open dialogue with secular philosophy, literature, and the arts. Camus is taken to be a more pertinent dialogical partner than Calvin, Wittgenstein than Luther, Nietzsche, Heidegger, and Whitehead than Thomas, Barth, and Tillich.”